The Indexer forty years ago (April 1983). (1st March 2023) - Bell, Hazel K.
Abstract : Hazel Bell, editor of The Indexer from 1978 to 1995, reflects on the content of the journal 40 years ago. In this issue, she travels back to April 1983. Reflections on past issues are a regular feature in the journal. You can look further back in time with the ' The Indexer forty years ago' series, which started in the September 2021 issue, or ' The Indexer thirty years ago' series, which was published from 1991 to 2008.